Analisis Perbandingan Pertumbuhan Dana Pihak Ketiga dan Profitabilitas Sebelum dan Sesudah Penerapan Program Laku Pandai pada BRI Syariah KCP Pati Jawa Tengah - Riayatul Insiroh; Ari Kristin Prasetyoningrum; Arif Afendi (P3M Politeknik Negeri Banjarmasin, 2021)
The development of the banking industry should have been matched by the improvement of banking service for the whole society. “Laku Pandai” is coming as a solution for all people to experiencing the benefits of financial services. With a non-office based service it is expected to increase public absorbtion funds, therefore it can increase the banking profits. This study aims to determine thedifference between the growth of third-party funds and profitability before and after the implementation of Laku Pandai in BRI Syariah. This type of research is quantitative by using secondary data in the form of financial statements from 2013 until 2019. The techniques used are purposive sampling and comparative method with a paired sample t-test parametric statistical test. The resultsshowed that there was a significant difference in the growth of third party funds (DPK) before and after the implementation of Laku Pandai. While there is no difference in profitability growth (ROA) before and after the implementation of Laku Pandai.